Glutathionyl-S-chlorogenic acid is present in fruit of Vaccinium species, potato tubers and apple juice. (15th November 2020) - McDougall, Gordon.J.; Foito, Alexandre; Dobson, Gary; Austin, Ceri; Sungurtas, Julie; Su, Shang; Wang, Lijin; Feng, Chengyong; Li, Shanshan; Wang, Liangsheng; Wei, Wei; Allwood, J. William; et al.
Highlights: A novel glutathionyl-chlorogenic acid conjugate is reported in blueberry fruit. The conjugate appears identical to an in vitro synthesised conjugate. The conjugate is also present at appreciable levels in potato tubers and apple juice. The biological function/bioactivity of this ubiquitous component is discussed. Abstract: A hydroxycinnamate-like component was identified in highbush blueberry ( Vaccinium corymbosum ) fruit, which had identical UV and mass spectrometric properties to an S-linked glutathionyl conjugate of chlorogenic acid synthesized using a peroxidase-catalyzed reaction. The conjugate was present in fruits from all highbush blueberry genotypes grown in one season, reaching 7–20% of the relative abundance of 5-caffeoylquininc acid. It was enriched, along with anthocyanins, by fractionation on solid phase cation-exchange units. Mining of pre-existing LC-MS data confirmed that this conjugate was ubiquitous in highbush blueberries, but also present in other Vaccinium species. Similar data mining identified this conjugate in potato tubers with enrichment in peel tissues. In addition, the conjugate was also present in commercial apple juice and was stable to pasteurization and storage. Although glutathionyl conjugates of hydroxycinnamic acids have been noted previously, this is the first report of glutathionyl conjugates of chlorogenic acids in commonly-eaten fruits and vegetables.